Gas chromatography-tandem mass spectrometry multiresidual method for determination of pesticide residues in honey - Helena BAŠA ČESNIK; Veronika KMECL (Acta Agriculturae Slovenica)
In our laboratory we introduced and validated a new analytical method for determination of environmental pesticide residues in honey. The extraction was conducted using acetone, petroleum ether and dichlorometane. The determination was conducted using gas chromatography coupled with tandem mass spectrometry. Practical usage of method was analyses of 31 samples of Slovenian honey. 33 active substances (pesticides) were sought. The insecticide cypermethrin was the only active substance found in three samples. The active substances sought were not found in 90.3 % of the samples analysed. The risk assessment showed that no unacceptable risk is expected for consumers. The results were compared with those from the literature. We revealed that honey from Slovenia contained a lower portion of positive samples per active substance sought as in Italy, comparable as in Estonia and Spain, comparable to higher as in Poland and higher as in Egypt.